(3HTQi GddHjH HPcQ GdMHjHs - (3eMeO Hf eMeO Hf eMeO Hf CMeO, GHf nSpqjO GdfGS, GdjYeQj GdQHYj, CHh GdaJM, aJM GdOjf,J (B734 (3g` s ((3GHf aGVd Gddg GdYeQi GdbQTi GdTGaYi s)
(3ChdgG (B:s
(3jG Ndjdi djdI GdLhRGA eG GMJjGdi ai GdebdI GdMhQGA s
(3BNQgG (B:s
(3heG CTQa GdHOQ GdefjQ cMSfg hCfi dg PGc GdLeGd eMGcjkG s
(3fSNI KGfjIs
(3hNRGFfjI cJH HQSe GdNRGfI GdDdDjI GdCejQjIs
(3hef BNQgG PcQ GdCMGOjK GdeJYdbI HGdeMHI ai Gddg JYGdi hecJHI JYGdi heMHI QShdgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B269s
(3GdLRA (B1 - (3U (B246 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B116 s
Keywords: (3GdCOHs